Implementation of the Classical Learning Model in Kindergarten - Lina (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The aim of this research is to describe the implementation of the classical learning model in kindergarten. Methodology: The method used in this research is descriptive quantitative and qualitative using questionnaires, observations and interviews as data collection techniques. Analysis of questionnaire and observation data uses statistical techniques, while interviews use interactive analysis. Main Findings: The implementation of the classical learning model in kindergarten is of "good" quality. The results of the questionnaire showed a percentage of 81% for general implementation, with a percentage of 75% for class setting indicators, 77% for teaching preparation indicators, and 93% for implementation process indicators. The observation results also showed "good" quality with a percentage of 83% in general, with a percentage of 64% for class setting indicators, 32% for teaching preparation indicators, and 70% for implementation process indicators. The interview results show that the school has implemented the classical learning model well, but there are shortcomings in using the latest curriculum and curriculum standards. Novelty/Originality of this study: The novelty of this research lies in the description of the implementation of the classical learning model in kindergarten and the analysis of its quality based on questionnaires, observations and interviews. This research provides a better understanding of the challenges and advantages of implementing classical learning models in early childhood education institutions with minimal teaching staff.